A dual water isotope dataset for quantifying summer water mass transport in the northern South China Sea - Sihai Liu; Chunqing Chen; Xuan Lu; Junhui Wu; Qibin Lao; Shangjun Cai; Fajin Chen (Scientific Data)
Abstract Dual water isotopes (δ¹⁸O, δ²H, referred to as δD) serve as robust tracers for water masses, enabling the identification and quantification of ocean currents and circulation patterns, thereby complementing traditional temperature-salinity and velocity metrics. This study presents a comprehensive dual water isotope dataset covering the northern South China Sea (SCS) to quantify summer water mass transport, addressing the scarcity of isotope observations in this region. The dataset comprises 873 dual isotope samples collected from 169 stations during summer (2015–2021), covering depths of 0–3700 m. Core parameters include δ¹⁸O, δD, temperature, and salinity. Additionally, using uniform end-member selection criteria and an isotope correction method, we applied the SIAR isotope mixing model to quantify the contributions of distinct water masses and characterize circulation features. This dataset fills a critical gap in SCS isotope data and establishes a standardized methodology for quantitatively interpreting water mass transport using dual water isotopes, underscoring the significance of isotopes as supplementary indicators for monitoring ocean currents and circulation dynamics.